1925 Tenn. Priv. Acts 298, vol. 1, An Act to Create and Incorporate the City of Brownsville, in Haywood County, Tennessee . . . , ch. 92, § 25, pt. 21. - (:unkn) unknown (My University, 1925)
To regulate the storage and transportation of illuminating oil and gunpowder and other high explosives, and to regulate and prohibit the use of firearms.
Keywords: GUNPOWDER - STORAGE